(untitled) (Research, Society and Development, 2020)
The Zona da Mata Pernambucana stands out for offering rich soils for planting sugar cane, due to its great social, economic and environmental importance for the country. The high representativeness of sugarcane in the value of production compared to other products from temporary crops, corroborate the economic importance in the micro-region. Using data from the website of the Brazilian Agricultural Research Corporation (Embrapa), this study aims to analyze whether there is a significant difference in terms of production of sugarcane, in tons/ha, between the periods 1990-2003 and 2004- 2017, in the micro-region of Vitória de Santo Antão/PE, Brazil. For the analysis, it was necessary to evaluate the two periods independently. Thus, the statistical software IBM SPSS STATISTICS 23 was used in order to assess the normality of the data through the Shapiro-Wilk test, which indicated that the data do not follow normality at the 0.05 significance level. Consequently, the Mann-Whitney test was applied, as it is a non-parametric test and considers the independence of the years. The results obtained by the test, with an exact significance of 0.94, indicated that there is no significant difference between the periods, that is, the microregion maintains the production of sugarcane each year, which makes the permanence of the cultivation of sugar cane for it.